PENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI KOOPERATIF TIPE PROJECT BASED LEARNING (PjBL) PADA SISWA KELAS V SD N 270 AEK BARU JULU KABUPATEN MANDAILING NATAL - Nurbaiti .; Samakmur .; Sabri .; , Ali Ahmad Fauzi (JURNAL MathEdu (Mathematic Education Journal), 2023)
This study aims to find out the real picture of 1) For the application of cooperative type Project Based Learning (PjBL) on the material of building a flat side space in class V SD N 270 Aek Baru Julu, Mandailing Natal Regency, 2) To determine the improvement of students' mathematics learning outcomes using cooperative the type of Project Based Learning (PjBL) on the material of building a flat side space in class V SD N 270 Aek Baru Julu, Mandailing Natal Regency. The type of research is Classroom Action Research (CAR), the object of this research is all fifth grade students of SD N 270 Aek Baru Julu, Mandailing Natal Regency, 2021-2022 Academic Year, . Furthermore, the subject was determined because the author saw that the students' mathematics learning outcomes in the flat-sided space building material were very low. The instrument used as a data collection tool is a test, observation. Student Learning Outcomes in the Cognitive Level (C2) Material of Constructing Flat Side Spaces Increasing Using Project Based Learning (PjBL) in Class V SD Negeri 270 Aek Baru Julu for the Academic Year 2021-2022 which is marked by the students' completeness in each cycle, namely in the first cycle they get a percentage 33.33% and in the second cycle it increased to 83.33%